Length‐weight relationships of three freshwater fish species from the Cujubim Sustainable Development Reserve, Amazonas, Brazil. (23rd February 2018) - Andrade, M. C.; Jesus, A. J. S.; Bastos, D. A.; Trindade, P. A. A.; Giarrizzo, T.
Summary: Length–weight relationships (LWR) were provided for three fish species from Cujubim Sustainable Development Reserve, drainages of the Jutaí River Basin, a tributary of the Solimões River, part of the Central Amazon Biodiversity Corridor, Amazonas, Region North of Brazil. Specimens were collected in March 2006 using gill nets with mesh sizes range between 2 and 18 cm. The LWRs for all species are provided by the first time, and two new maximum length are recorded.